Syntactic structure and rhetorical combinations of Iranian English research article titles in medicine and applied linguistics: A cross-disciplinary study - Moslehi, Shadab; Kafipour, Reza (Frontiers in Education, 2022)
This corpus-based cross-disciplinary study investigated the syntactic structures and rhetorical combinations of 200 research article titles in two disciplines, namely, medicine (100) and applied linguistics (100). The RA titles were selected from four reputable Iranian English journals. The authors were all Iranian researchers in these two disciplines. The titles were analyzed in light of Dietz taxonomy. First, the frequencies and percentages of each syntactic and rhetorical construction occurrence have been calculated. Next, the authors performed a t-test regarding title length and the chi-square test to decide whether syntactic or rhetorical construction is a discipline-specific convention. The findings revealed thatmedical titles were longer than the linguistic ones. The frequency and percentage of both single- and multi-unit RA titles were essentially the same in both disciplines. Concerning the syntactic components of single-unit RA titles, the most frequently used structure was the nominal construction, followed by verbal and prepositional ones. The most recurrent syntactic components of the nominal structure in both disciplines were post- and pre-modified, with medical titles overtaking the linguistic titles in all nominal categories. In terms of verbal constructions, the dominant structure in medicine was the full sentence, and in applied linguistics, gerund phrases. Regarding the rhetorical components of multi-unit RA titles, medical titles took precedence over the linguistic titles in using the topic method. The topic scope and topic description organization are mostly reported in applied linguistics titles. In this study, however, two new rhetorical combinations were identified. The chi-square test results only confirmed the verbal structures of single-unit and the rhetorical combinations of multi-unit RA titles as distinctive features for each discipline.